Sustainability of total factor productivity in the countries of the MENA region with an emphasis on ecological footprint - Fatemeh Fathi; Effat Ghorbanian (علوم محیطی)
Introduction: Sustainable growth takes into account resource development, the environment, and the economy. In this century, enormous ecological destruction and the accelerated depletion of natural resources have affected global economic growth, social welfare, and improvements in human health. In some studies, traditional total factor productivity has used the gross domestic product as desirable outputs, and energy, capital, and labor as inputs. Gross domestic products as desirable outputs are biased against sustainable growth because sustainable growth requires not only gross domestic product growth but also human well-being improvements. Hence the human development index has more advantages compared to gross domestic product. The ecological footprint is an index that measures the degree of sustainable development. In an attempt to overcome the limitations of the gross domestic product as output and energy as inputs, this paper took ecological footprint as the index of comprehensive ecological inputs and used the human development index as the output index. It used a new index, Sustainable Total Factor Productivity (STFP), to reflect sustainable growth levels.Material and methods: This paper combines the ecological footprint and human development index with Total Factor Productivity (TFP) to use a new framework for STFP. We used a DEA-Malmquist index method to calculate STFP changes in MENA countries during the years 1995–2016 and a σ-convergence test method to test the STFP convergence trends for them. We defined the Sustainable Malmquist (SM) index, as a measure of STFP change. SM can be decomposed into sustainable efficiency change and sustainable technical change.Results and discussion: Overall, the average annual STFP in MENA countries was 0.98, indicating that from the perspective of ecological footprint, K, and L are input factors, and the human development index (HDI) is the output. All states emphasize a little on sustainable growth except Bahrain and Turkey. Bahrain ranked first, having the highest average Sustainable Malmquist index, and then Turkey ranked second. Bahrain's capital increased by 75 %. After decomposing SM into Sustainable Technical Change (STC), Sustainable Pure Technological Efficiency Change (SPEC), and Sustainable Scale Efficiencychange (SSEC) , the average STC value was 0.996 meaning that sustainable technology change was stagnant. SPEC had an average value of 1.00, showing that sustainable efficiency has improved. On average, the SSEC was 0.98, indicating that industry structure and scale effects may have not improved. Contraries on the category of very high and medium HDI states, had higher STC than that for the category high and low HDI states, suggesting that developed states are superior in terms of STC. Category of high HDI, developed nations with human development index more than 0.8, had an average SPEC value of 1.00. The sustainable growth gap between developing states was the greatest. The σ value of medium HDI states containing Iran was the smallest and showed minimal volatility. This indicates that the sustainable growth gap between developed states was small and relatively balanced. The σ values of very high and medium HDI categories fluctuated widely. This indicates that growth in developing states and developed states was not stable.Conclusion: Different types of nations should choose different paths to achieve positive sustainable growth. The STFPs of the MENA nations present different features according to different economic levels and environmental protection levels, so formulating distinguished policies of sustainable growth is a necessity. Technical progress should be promoted to achieve sustainable growth. Promoting sustainable technology plays a crucial role in sustainable growth. Policymakers should encourage research, develop sustainable technologies, and raise entrepreneur awareness of eco-environmental protection.